Pendidikan kesehatan dengan teknik bermain kartu edukasi dapat membentuk perilaku jajanan sehat pada anak usia sekolah - Dewi Marianthi; Ismail Ismail; T Alamsyah; Wirda Hayati (AcTion: Aceh Nutrition Journal, 2020)
The behavior of school-age snacks, for the most part, does not meet health requirements, so there is a risk of various health problems or diseases. The need for health education for appropriate school-age children to shape healthy snacks, one of which is by playing. The objective research an after community service, it is expected that school-age children consume healthy snacks while in school. Methods, the research design was quasi-experimental, the treatment group received an intervention in the form of providing health education about healthy snacks through playing techniques using educational cards, using healthy snacks, while the control group was carried out with health education about distributing leaflets. The study sample of 100 people consisted of 50 intervention groups and 50 in the control group—analysis data using Dependent T-Test. Results, there were differences in healthy snack behavior before and after treatment, and there were differences in scores of the value of the knowledge, skills, and attitude variables about healthy snacks before and after treatment (p= 0,001), between the intervention group and the control group. In conclusion, there is an increase in the amount of knowledge, attitudes, and behaviors of healthy snacks for Banda Aceh students after providing health education. Suggestion, there needs to support from all of the institutions had related to form healthy snacks behavior among all students in elementary school.